Soil potassium fractions under two contrasting land use systems of Assam - DAS, ANSHUMAN; BISWAS, D R; SHARMA, V K; RAY, PRASENJIT (The Indian Journal of Agricultural Sciences, 2019)
Potassium (K) plays an important role in growth, yield, quality, osmotic regulation, ionic balance and stress resistance of crops. Fertilizer application in Indian agriculture has remained largely skewed towards nitrogen (N) and phosphorus (P), while K remained neglected for over last five decades. On this background, the present study evaluates the soil K fractions under two contrasting land use systems, viz. rice-fallow and forest under three soil depths (0-15, 15-30 and 30-60 cm) and categorisation of soils based on exchangeable K (Exch-K) and non-exchangeable K (NEK) with the strategy for proper K management. Results indicated that the soils of rice-fallow land use system were present in a category which is low in both Exch-K and NEK and as a result it requires adequate K fertilization. Both Exch-K and NEK were higher in the forest soils as compared to rice-fallow soils in the three soil depths. The ratio of NEK/Exch-K was higher in the forest than rice-fallow land use system. The ratio was increased with increase in depth in the forest land use system which indicates that it has more potential to supply subsoil K in long term. This categorisation of soils into different groups provides a comprehensive assessment of K availability for different land use systems and better recommendation of K fertilizer for efficient K management.